Maternal Employment and Childhood Obesity among Immigrant Families - Zhang, PhD, Qi (North American Journal of Medicine and Science, 2010)
There are continued interests to examine the relationship between maternal employment and childhood obesity. However, little research has been focused on childhood obesity among immigrant families with working mothers. This study used the Panel Survey of Income Dynamics (PSID) and Child Development Supplement (CDS) in 2002 and compared the impact of maternal employment on childhood obesity between immigrant families and US-born families. The positive effect of maternal employment on children’s body weight status was much stronger in immigrant families than in US-born families. The full-time employment status of mothers had strong and significant effect on immigrant children’s BMI (beta = 3.33, P<0.05). In immigrant families, unemployed mothers had a significantly positive effect on the likelihood of childhood overweight (OR = 4.09, P<0.01). However, in US-born families, unemployed mothers had a significantly negative effect on childhood overweight (OR = 0.87, P<0.01). Acculturation and lack of access to social welfare might explain the additional positive contributions of working mothers to childhood obesity in immigrant families.